Productivity and suitability assessment of orange (Citrus reticulata)- growing soils in Nagpur - LIKHAR, CHETNA K; PRASAD, JAGDISH (The Indian Journal of Agricultural Sciences, 2011)
Six pedons were evaluated for their productivity and suitability on the basis of variation in physiography, parent materials, soils and productivity of oranges in Nagpur district of Maharashtra. The pedons were shallow underlain by saprolite (P3, P4 and P5) and deep (P1, P2 and P6) classified as Vertisols (P1 and P2), Inceptisols (P3 and P6) and Alfisols (P4 and P5). In general, sand, silt and clay contents ranged from 0.6 to 46.1, 19.3 to 40.0 and 24.1 to 68.2% in different horizons, respectively. The soils were moderately acidic to moderately alkaline in reaction associated with sodicity in sub-soils (P1 and P6). The CEC varied from 18.3 to 59.3 cmol (p+)/kg. The available N, P and K ranged from 50.2 to 250.9, 0.8 to 27.7 and 252.0 to 1 030.4 kg/ha, respectively in different pedons. The Riquier productivity index appears to be more reliable as compared to Storie index and these ratings are not in reliance with the Sys and proposed suitability criteria and yield of oranges realized. On computation of the existing limitations, a new criterion has been proposed (against Sys suitability criteria for Citrus spp) which indicated that P3, P4 and P5 were moderately suitable and others were marginally suitable.